Suppression of Sestrins in aging and osteoarthritic cartilage: dysfunction of an important stress defense mechanism. Issue 2 (February 2017) - Shen, T.; Alvarez-Garcia, O.; Li, Y.; Olmer, M.; Lotz, M.K.
Summary: Objectives: Aging is an important osteoarthritis (OA) risk factor and compromised stress defense responses may mediate this risk. The Sestrins (Sesn) promote cell survival under stress conditions and regulate AMP-activated protein kinase (AMPK) and mammalian target of rapamycin (mTOR) signaling. This study examined Sesn expression in normal and OA cartilage and functions of Sesn in chondrocytes. Methods: Sesn expression in human and mouse normal and OA cartilage was analyzed by quantitative polymerase chain reaction (PCR) and immunohistochemistry. Sesn function was investigated by using small interfering RNA (siRNA) mediated Sesn knockdown and overexpression with analysis of cell survival, gene expression, autophagy, and AMPK and mTOR activation. Results: Sesn mRNA levels were significantly reduced in human OA cartilage and immunohistochemistry of human and mouse OA cartilage also showed a corresponding reduction in protein levels. In cultured human chondrocytes Sesn1, 2 and 3 were expressed and increased by tunicamycin, an endoplasmic reticulum (ER) stress response inducer and 2-deoxyglucose (2DG), a metabolic stress inducer. Sesn1 and 2 were increased by tBHP, an oxidative stress inducer. Sesn knockdown by siRNA reduced chondrocyte viability under basal culture conditions and in the presence of 2DG. Sesn overexpression enhanced LC3-II formation and autophagic flux, and this was related to changes in mTOR but not AMPK activation. Conclusion: These findings are the first to show that Sesn expression is suppressed in OA affected cartilage. Sesn support chondrocyte survival under stress conditions and promote autophagy activation through modulating mTOR activity. Suppression of Sesn in OA cartilage contributes to deficiency in an important cellular homeostasis mechanism.